Received sensitivity: adapting Ainsworth's scale to capture sensitivity in a multiple-caregiver context. Issue 2 (3rd March 2016) - Mesman, Judi; Minter, Tessa; Angnged, Andrei
ABSTRACT: A network of multiple caregivers contributing to the care of an infant is the norm in many non-Western cultural contexts. Current observational measures of caregiver sensitive responsiveness to infant signals focus on single caregivers, failing to capture the total experience of the infant when it comes to the sensitive responsiveness received from multiple sources. The current paper aims to introduce the construct of received sensitivity that captures the sensitivity that an infant experiences from multiple sources in cultural contexts where simultaneous multiple caregiving is common. The paper further presents an adaptation of Ainsworth's Sensitivity versus Insensitivity observation scale to allow for the assessment of sensitivity as received by the infant regardless of who is providing the sensitive responses to its signals. The potential usefulness of the Received Sensitivity scale is illustrated by two case studies of infants from an Agta forager community in the Philippines where infants are routinely taken care of by multiple caregivers. The case studies show that the infants' total experience of being responded to sensitively cannot be simply derived from the sum of individual caregiver sensitivity scores, demonstrating the potential added value of the new Received Sensitivity observation measure.